Health System in the Cities of Uzbekistan: Status and Issues (1950–1980) - Anora Zayniddinovna Togaeva (International Journal on Integrated Education, 2022)
From the mid-twentieth century to the 190s, the health care system and public utilities in Uzbekistan underwent unique development. During this period, important measures were taken to protect and restore public health and prevent various diseases. However, due to a number of factors, the development of the field has been very challenging. This article describes the situation in the health care system using the example of large cities in Uzbekistan and analyses the problems associated with this.